De Madagascar à Sumatra : une route négrière peu commune. Le voyage du navire Binnenwijzend de la VOC en 1732 - Rafaël Thiébaut (Afriques)
In 1732 the Dutch East India Company (VOC) ship Binnenwijzend undertook a slaving voyage to Madagascar in order to furnish the gold mines of Sumatra with manpower. By using unique and unpublished archival material we have been able to retrace the dynamics of this exceptional slaving expedition, from the armament to her return to Batavia. Thanks to this voyage, we can learn a lot on the political and economic situation of the Sakalava people of Madagascar as well as that of the VOC. Together with other data compiled from similar expeditions, this voyage allows us to better understand the commercial interactions between Dutch merchants and Malagasy sovereigns during a poorly known period when maritime trade with Europeans was developing rapidly. Finally this evidence gives us more unique details on the conditions of slaves during an uncommon middle passage.